Unlocking the power of probiotics, postbiotics: targeting apoptosis for the treatment and prevention of digestive diseases - Xie, Qiuyan; Liu, Ji; Yu, Ping; Qiu, Ting; Jiang, Shanyu; Yu, Renqiang (Frontiers in Nutrition, 2025)
Digestive diseases are becoming an increasingly serious health burden, creating an urgent need to develop more effective treatment strategies. Probiotics and postbiotics have been extensively studied for their potential to prevent and treat digestive diseases. Growing evidence suggests that programmed cell death, especially apoptosis, is a critical mechanism influencing the molecular and biological aspects of digestive diseases, contributing to disease progression. Understanding the mechanisms and signaling pathways by which probiotics and postbiotics regulate apoptosis could reveal new therapeutic targets for treating digestive diseases. This review focuses on the beneficial effects of probiotics and postbiotics in regulating apoptosis across a range of liver diseases, including non-alcoholic fatty liver disease, liver injury, cirrhosis, and liver cancer. It also explores their effects on gastrointestinal diseases, such as colorectal cancer, colitis, gastrointestinal injury, and infectious diarrhea. Furthermore, some probiotics help balance the gut microbiota, enhance intestinal barrier function, and regulate the immune system, all of which are closely associated with apoptosis. Moreover, emerging technologies, such as encapsulation methods, have been developed to stabilize probiotics, primarily based on experimental findings from rodent and human studies.